Biochar Optimizes Wheat Quality, Yield, and Nitrogen Acquisition in Low Fertile Calcareous Soil Treated With Organic and Mineral Nitrogen Fertilizers - Khan, Mushtaq Ahmad; Basir, Abdul; Fahad, Shah; Adnan, Muhammad; Saleem, Muhammad Hamzah; Iqbal, Anas; Amanullah,; Al-Huqail, Asma A.; Alosaimi, Areej A.; Saud, Shah; Liu, Ke; Harrison, Matthew Tom; et al. (Frontiers in Plant Science, 2022)
Crop quality and nutrients uptake are considerably influenced by fertilizers inputs and their application rate. Biochar (BC) improves nitrogen uptake and crop productivity. However, its interaction with synthetic and organic fertilizers in calcareous soil is not fully recognized. Therefore, we inspected the role of biochar (0, 10, 20 and 30 t ha-1) in improving N uptake and quality of wheat in calcareous soil under integrated N management (90, 120, 150 kg N ha-1 applied each from urea, farm yard manure (FYM) and poultry manure (PM) along with control) in two years field experiment. Application of 20 t BC along with 150 kg N ha-1 as poultry manure considerably improved wheat grain protein content (14.57%), grain (62.9%), straw (28.7%) and biological (38.4%) yield, grain, straw and total N concentration by 14.6, 19.2 and 15.6% and their uptake by 84.6, 48.8 and 72.1% respectively, over absolute control when averaged across the years. However, their impact was more pronounced in 2nd year (2016-17) after application compared to 1st year (2015-16). Therefore, for immediate crop benefits, it is recommended to use 20 t BC ha-1 once in 50 years for enhancing nitrogen use efficiency of fertilizers and crop yield.